Incline and decline running alters joint moment contributions but not peak support moments in individuals with an anterior cruciate ligament reconstruction and controls - Harrison, Kenneth; Holmes, Hillary H.; Finley, Eric B.; Guzman, Keven Santamaria; Kimbrough, Katherine C.; Roper, Jaimie A. (Frontiers in Sports and Active Living, 2023)
Individuals with anterior cruciate ligament reconstruction (ACLR) commonly exhibit altered gait patterns, potentially contributing to an increased risk of osteoarthritis (OA). Joint moment contributions (JMCs) and support moments during incline and decline running are unknown in healthy young adults and individuals with an ACLR. Understanding these conditional joint level changes could explain the increased incidence of OA that develops long-term (Erhart-Hledik et al., 2018; Teng et al., 2017). Therefore, this knowledge may provide insight into rehabilitation and prevention of osteoarthritis development. We aimed to identify interlimb and between-group differences in peak support moments and subsequent peak ankle, knee, and hip JMCs between individuals with an ACLR and matched controls during different sloped running conditions. Seventeen individuals with unilateral ACL reconstruction and 17 healthy individuals matched based on sex, height, and mass participated. Participants ran on an instrumented treadmill at an incline of 4°, decline of 4°, incline of 10° and decline of 10°. The last ten strides of each condition were used to compare whole-stance-phase support moments and JMCs between limbs, ACLR and control groups, and across conditions. No differences in JMCs were identified between limbs or between ACLR and healthy control groups across all conditions. Support moments did not change among the different sloped conditions, but joint moment contributions significantly changed. Specifically, ankle and knee JMCs decreased and increased by 30% and 33% from an incline of 10° to a decline of 10° running. Here, the lower extremities can redistribute mechanics across the ankle, knee, and hip while maintaining consistent support moments during incline and decline running. Our data provides evidence that those with ACLR do not exhibit significant alterations in joint contributions while running on sloped conditions compared to matched controls. Our findings inform future research interested in understanding the relationship between sloped running mechanics and the incidence of deleterious acute or chronic problems in people who have an ACLR.